The Effect Of Service Quality On Customer Satisfaction (Survey of Bank Mandiri Customers, Sutisna Senjaya Branch) - Haq, Teguh Zaenul; Pauzy, Depy Muhamad; Lestari, Suci Putri (Utami Publisher, 2024)
The Purpose Of This Study Was To Determine The Description Of Service Quality And Customer Satisfaction At Mandiri Bank Brach Sutisna Senjaya And To Determine The Effect Of Service Quality On Customer Satisfaction At Mandiri Bank Brach Sutisna Senjaya. The Research Method Used By Researchers Is To Use Descriptive Analysis. This Research Uses A Quantitative Approach. The Type Of Research Used In This Research Is Causal. In This Study, The Authors Conducted Direct Research On All Mandiri Bank Customers To Obtain Data. The Sample In This Study Was 50 People, This Is Based On Saturated Sampling Technique Where The Population In This Study Was 50 People. Researchers Will Conduct Tests Using SPSS Version 25. Service Quality At Mandiri Bank Brach Sutisna Senjaya Is Currently In A Very Good Classification. Mandiri Bank Customer Satisfaction Is Currently In A Good Classification Because Customer Service Maintain Satisfaction At Mandiri Bank. Service Quality Has A Significant Effect On Customer Satisfaction Because If The Implementation Of Service Quality Will Increase Customers Who Are Satisfaction To The Program Provided By Mandiri Bank Brach Sutisna Senjaya.